(untitled) (World Economics and Finance Bulletin, 2023)
The study aimed to explore the contribution of the entrepreneurial approach as an independent variable through its dimensions (creativity, proactiveness, risk-taking) to institutional excellence as a dimension variable (leadership, human and service provision excellence) at Tikrit University, and researchers used the analytical descriptive approach to interpret data obtained through the questionnaire. The study community is represented and appointed by the administrative leaders of Tikrit University (75) individual representatives (the rector, his assistants, deans of colleges, their collaborators, the duration of departments and administrative centers of the university). An electronic questionnaire was distributed to the study sample and obtained an answer percentage (100%), The study’s comprehensive accounting method was used. The study reached a set of conclusions, most notably the increasing importance of leadership in achieving institutional excellence at Tikrit University through its role in building creative and innovative capabilities that will strengthen the university’s orientation towards adopting an initiative and proactive approach and seizing market opportunities that will enhance scientific and academic advancement . The study also recommends that the University should encourage its administrative and academic associates to initiate and engage in bold activities that are of a degree of risk and acquire and benefit from the experience of scientific experiments in the future